(untitled) (Czech Journal of Multidisciplinary Innovations, 2025)
Our research aims to investigate black tourism for the Speicher site in Iraq, to develop strategies for the site of the heinous terrorist crime in the Speicher area in Saladin Governorate, which gave a new concept to tourism represented by black tourism, as well as to shed light on the events that took place at this site, which was filled with sadness and tragedy. Tears flowed at his remembrance, and hearts went towards him, as thousands of families, individuals, celebrities, artists, and senior officials came to commemorate the anniversary of this tragedy.